2019
DOI: 10.1590/0034-737x201966010002
|View full text |Cite
|
Sign up to set email alerts
|

Identificación de Peronospora sparsa y evaluación del contenido de fenoles en frutos de mora de castilla afectados por este microorganismo

Abstract: Identificación de Peronospora sparsa y evaluación del contenido de fenoles en frutos de mora de castilla afectados por este microorganismo La enfermedad mildeo velloso en mora de castilla es causada por patógenos pertenecientes al género Peronospora, el cual genera graves pérdidas en periodos cortos y afecta principalmente hojas, tallos y frutos; además, la presencia de agentes infecciosos ocasiona estrés en las plantas, activando la síntesis de metabolitos secundarios como mecanismo de defensa. El objetivo de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Next, the samples were dried with CO 2 in a critical point desiccator (Sandri-780A, USA) for 40 min and placed in a copper sample holder and coated with gold in an ionizer (Ion Sputter JFC-1100, JEOL, Japan) for 1 min. Finally, the preparations were observed and photographed in a scanning electron microscope, FEI model Quanta 250 (Thermo Fisher Scientific, Japan) as described by Cardona-Hurtado et al [14], and the structures observed were compared with those reported by Fierro-Corrales et al [15].…”
Section: Methodsmentioning
confidence: 99%
“…Next, the samples were dried with CO 2 in a critical point desiccator (Sandri-780A, USA) for 40 min and placed in a copper sample holder and coated with gold in an ionizer (Ion Sputter JFC-1100, JEOL, Japan) for 1 min. Finally, the preparations were observed and photographed in a scanning electron microscope, FEI model Quanta 250 (Thermo Fisher Scientific, Japan) as described by Cardona-Hurtado et al [14], and the structures observed were compared with those reported by Fierro-Corrales et al [15].…”
Section: Methodsmentioning
confidence: 99%